A Two-Stage Bedside Intubation Method to Improve Success Rate of Post-pyloric Placement of Spiral Nasoenteric Tubes in Critically Ill Patients: A Multi-Center, Prospective Study - Xu, Jing; Li, Sinian; Chen, Xiangyin; Tan, Bo; Chen, Shenglong; Hu, Bei; Nie, Zhiqiang; Ye, Heng; Sun, Cheng; Chi, Ruibin; Chen, Chunbo (Frontiers in Medicine, 2022)
Abstract Backgrounds: Prokinetic agents could improve the success rate of post-pyloric placement of self-propelled spiral nasoenteric tubes (NETs), and bedside blind technique might apply as a rescue therapy subsequent to spontaneous transpyloric migration failure. The objective of this study was to investigated the validity and safety of these two bedside intubation methods as a sequential procedure for post-pyloric placement of spiral NETs in critically ill patients. Methods: The multicenter, prospective study was conducted in intensive care units of four tertiary hospitals (June 2020 to January 2021). Eligible patients received self-propelled spiral NET placements, promoted by prokinetic agents (Stage 1). An abdominal X-ray performed 24 h post-intubation confirmed the position of the tube tip. Patients with a failed transpyloric migration entered Stage 2, where beside blind intubation was conducted (reconfirmed by X-ray). The primary end point was the overall success rate of post-pyloric placement. Results: The overall success rate of post-pyloric placement of the spiral NET was 91.1% (73.4% in the third portion of the duodenum [D3] or beyond). The total adverse event rate was 21.0%, without any serious adverse events. In Stage 1, 55.6% of participants achieved transpyloric migration, of these, 44.4% migrated to D3 or beyond. The median time from decision to intubate to the initiation of enteral nutrition (EN) was 25 h. In Stage 2, 83.0% of patients had successful post-pyloric intubation (67.9% in D3 or beyond). The median time from decision to EN initiation after the two-stage process was 36 h. Conclusions: Prokinetic agents-assisted self-propelled intubation and remedial bedside blind technique as a sequential procedure for post-pyloric placement of spiral NETs were effective and safe, and this two-stage process did not affect the implementation of early EN in critically ill patients. Keywords: Self-propelled nasoenteric tubes, Prokinetic agents, Blind bedside, Post-pyloric placement, Enteral nutrition, Critically ill patients.